Theurgy in the medieval Islamic world: conceptions of cosmology in Al-Būnī’s Doctrine of the Divine Names - Martin III, John Daniel (AUC Knowledge Fountain, 2011)
The mystical cosmology set forth by Abu-l-ʿAbbās Aḥmad b. ʿAlī b. Yūsuf al-Qurashī al-Būnī (d. 622 / 1225) is of tremendous importance for understanding the development and application of the medieval Islamic occult sciences. In this thesis, we explore the concept and purpose of medieval Islamic theurgy as it is presented by al-Būnī. We will attempt to contextualize it within its complex and nuanced cosmology. His widely distributed and often banned work Shams al-maʿārif presents a challenge to even the most adept reader as it requires advanced understanding in an array of seemingly disparate subjects. This and other of al-Būnī’s works represent a comprehensive, albeit roundabout, guide to medieval Islamic occult philosophy and theurgic rites. The body of work as whole, dubbed the ‘Corpus Bunianum’ by Jan Just Witkam, problematically suffers from lack of critical scholarship and confusion within its textual tradition. We will offer an introductory analysis of the textual tradition and a list of titles which can be reasonably attributed to al-Būnī, along with some information regarding their manuscript tradition